Recurrent diffuse pigmented villonodular synovitis of the knee with posterior extension: clinical outcomes following arthroscopic synovectomy with radiosynoviorthesis and platelet rich plasma- a case report - Saran, J. S. R. G.; Kumar, Yashavantha; Gowdara, Goutham; Varma, Jampuram Sethumadhava; Chaudhuri, Anjan; Divaker, Rishith (International Journal of Research in Orthopaedics, 2026)
Pigmented villonodular synovitis (PVNS) is a rare, benign, and locally aggressive synovial disorder that most commonly affects the knee. The diffuse form carries a high recurrence risk and is challenging to treat, particularly when the posterior compartments are involved. A 29-year-old man presented with recurrent right knee stiffness and swelling without pain, five years after his second arthroscopic synovectomy for diffuse PVNS. MRI revealed extensive synovial proliferation involving the suprapatellar pouch and posterior knee compartment along the posterior cruciate ligament (PCL). He underwent arthroscopic synovectomy using a posterior trans-septal portal for complete posterior access, followed by radiosynoviorthesis with phosphorus-32, structured physiotherapy and adjuvant platelet-rich plasma (PRP) injection. At five-year follow-up, MRI showed moderate residual synovial thickening; however, the clinical outcomes improved markedly. The IKDC score increased from 41.4% to 83.9% and the Tegner-Lysholm score increased from 44% to 94%. The patient regained pain-free ambulation and knee motion from 0° to 120°, with no recurrent swelling. Recurrent diffuse PVNS with posterior compartment involvement benefits from a multimodal approach that integrates advanced arthroscopic techniques and adjuvant therapies. Significant functional recovery is achievable despite residual radiologic changes, highlighting the value of comprehensive management and long-term follow-up.